2016
DOI: 10.1111/papr.12424
|View full text |Cite
|
Sign up to set email alerts
|

Management of Postherniorrhaphy Chronic Neuropathic Groin Pain: A Role for Dorsal Root Ganglion Stimulation

Abstract: Chronic neuropathic groin pain is a sequela of hernia surgery that occurs at unacceptably high rates, causing widespread impacts on quality of life. Although the medical community is beginning to recognize the role of surgical technique in the initiation and maintenance of postherniorrhaphy neuropathic pain, little information exists regarding pain management strategies for this condition. This review presents a summary of the pain condition state, its treatment options, and treatment recommendations. Both lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 81 publications
0
14
0
2
Order By: Relevance
“…DRG neurostimulation has been shown to effectively treat discrete areas of pain, such as the groin and foot, which are typically more difficult to treat with traditional SCS without causing discomfort in non‐painful regions . In these specific areas, our pooled analysis showed an 80% responder rate at one year.…”
Section: Discussionmentioning
confidence: 95%
“…DRG neurostimulation has been shown to effectively treat discrete areas of pain, such as the groin and foot, which are typically more difficult to treat with traditional SCS without causing discomfort in non‐painful regions . In these specific areas, our pooled analysis showed an 80% responder rate at one year.…”
Section: Discussionmentioning
confidence: 95%
“…Technical barriers relating to placing the leads adjacent to the DRG were overcome though development of a specifically designed lead delivery system. Initial studies, which have been encouraging, showed sustained pain relief in patients with focal neuropathic pain, such as CRPS and groin pain, which are traditionally difficult to treat with conventional SCS . In a recent prospective RCT, which led to U.S. Food and Drug Administration approval, Deer et al .…”
Section: Drg Stimulationmentioning
confidence: 99%
“…Initial studies, which have been encouraging, showed sustained pain relief in patients with focal neuropathic pain, such as CRPS and groin pain, which are traditionally difficult to treat with conventional SCS. [166][167][168][169][170] In a recent prospective RCT, which led to U.S. Food and Drug Administration approval, Deer et al 12 demonstrated that in patients with CRPS, DRG stimulation was superior to conventional SCS for the primary composite outcome (≥ 50% reduction in VAS score from baseline for the trial and at 3 months after implantation; lack of neurologic deficits) and for secondary end points, including positional effects on paresthesia, quality of life, emotional scales, satisfaction, stimulation specificity, and percent change. The study is remarkable in that 81.2% of patients randomized to DRG SCS achieved success at 3 months, compared with 55.7% in those who received conventional stimulation, and these results were stable at 12 months.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Die Dorsalganglienstimulation ist eine wichtige Neue rung, mit der es erstmals möglich ist, kleine, abgeschlos sene Schmerzareale wie beispielsweise Knie oder Leisten schmerzen gezielt zu behandeln. Obwohl diese Stimula tionsform erst seit wenigen Jahren zur Verfügung steht, gibt es hierzu eine große Anzahl von Studien und Lang zeitergebnissen [29][30][31][32][33][34]. In einer Studie mit 62 Patien ten konnte gezeigt werden, dass über einen Zeitraum von 3 Jahren eine sehr gute Schmerzlinderung von mehr als 50 % erreicht werden konnte (p < 0,0001) [30].…”
Section: Dorsalganglienstimulationunclassified